Shipwrecks and Storytelling - Filipe Castro; Susana Medina (Heritage, 2022)
Shipwreck stories have the potential to attract the attention of a wide public in different ways. Based on the Portuguese situation, of a country with a mythical past connected to the sea but a public policy for maritime archeology that lacks vision, purpose, or strategy and tends to exclude the public, this paper proposes a reflection on the social value of archeology and the potential it has for education and entertainment.